Soil thermal properties affected by topsoil thickness in switchgrass and row crop management systems - Zaibon, Syaharudin; Anderson, Stephen H; Veum, Kristen S.; Haruna, Samuel I. (Elsevier, 2019)
Perennial systems, such as switchgrass have been shown to improve soil hydraulic properties on degraded soils relative to annual cropping systems; however, studies of the effects on thermal properties are limited. Therefore, the objectives of this study were to determine the effects of topsoil thickness on soil thermal properties under switchgrass (Panicum virgatum L.) and row crop production systems. The experiment was carried out at the University of Missouri South Farm Research Center (38°54′ N, 92°16′ W). Research plots were re-established in 2009 with selected topsoil thickness categorized into two treatments (shallow [4 cm] and deep [36 cm]) on a Mexico silt loam (Vertic Epiaqualfs). Plots were planted to either switchgrass or a corn (Zea mays L.)-soybean (Glycine max (L.) Merr.) rotation with four replicates. Undisturbed soil cores (7.6 by 7.6 cm) and bulk soil were collected from two depths (10 cm increments) to determine thermal properties. Thermal conductivity (λ), vo-lumetric heat capacity (C v), and thermal diffusivity (D) were measured at 0, −33, −100 and − 300 kPa soil water pressures. In addition, soil organic carbon (SOC), bulk density (D b) and water content (θ) were also determined. The results showed that the switchgrass treatment had 23% higher SOC, 5-8% greater θ, and 11% lower D b than the row crop treatment. In turn, switchgrass plot exhibited a 5-7% reduction in λ, an 8-9% reduction in D, and a 2-3% increase in C v. Shallow topsoil thickness demonstrated increased thermal properties (λ, D and C v) relative to the deep topsoil thickness, likely due to higher clay content in the surface soil horizon and associated higher θ. This study contributes to a better understanding of the impact of topsoil loss and perennial vegetation on the thermal properties of soils in degraded landscapes.